2020
DOI: 10.2147/cmar.s230849
|View full text |Cite
|
Sign up to set email alerts
|

<p>4E-BP1<sup>Thr46</sup> Phosphorylation Association with Poor Prognosis in Quantitative Phosphoproteomics of Portal Vein Tumor Thrombus Revealed that 4E-BP1Thr46 Phosphorylation is Associated with Poor Prognosis in HCC</p>

Abstract: These authors contributed equally to this work Purpose: Early formation of portal vein tumor thrombosis (PVTT) is a key characteristic of hepatocellular carcinoma (HCC) metastasis, but to date, the aetiology of PVTT in HCC metastasis is largely unknown. We aim to find highly sensitive and specific biomarkers for the prediction of HCC prognosis. Patients and methods: We used isobaric tags for relative and absolute quantitation (iTRAQ) based quantitative phosphoproteomics approach to investigate the molecular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Taking together, these data suggest high expressed p-eIF4E and p-4EBP1 could be new prognostic marker for NSCLC. Several research pointed out that overexpression of p-4EBP1 has been found in a range of other tumors, including ovarian cancer, hepatocellular carcinoma, and breast cancer, which confirmed their important role in various cancers [ 14 , 22 , 23 ]. In addition, 4EBP1 is associated with prognosis of patients in several kinds of cancers, such as renal cell cancer and small cell lung cancer [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 94%
“…Taking together, these data suggest high expressed p-eIF4E and p-4EBP1 could be new prognostic marker for NSCLC. Several research pointed out that overexpression of p-4EBP1 has been found in a range of other tumors, including ovarian cancer, hepatocellular carcinoma, and breast cancer, which confirmed their important role in various cancers [ 14 , 22 , 23 ]. In addition, 4EBP1 is associated with prognosis of patients in several kinds of cancers, such as renal cell cancer and small cell lung cancer [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 94%
“…HCC with early formation of portal vein tumor thrombosis (PVTT) had a higher risk of metastasis. Lin et al 67 performed a phosphorylated proteomic analysis and identified a total of 1,745 phosphoproteins in HCC tissues, normal tissues, and PVTT tissues. The results showed that HCC and PVTT tissues had higher phosphorylation levels of 4E-BP1 than surrounding noncancerous tissues.…”
Section: Recombinant Human Eukaryotic Translation Initiation Factor 4...mentioning
confidence: 99%
“…Aberrant protein phosphorylation is associated with HCC ( 142 ) and more phosphorylation alterations have been elucidated with the development of omics methods. Elevating phosphorylation levels of 4E-binding protein 1 (4E-BP1) on Thr46 could be used to predict the early recurrence and metastasis of HCC ( 68 ). The level of Ser36 phosphorylation of aldolase A (ALDOA) was increased and could be used as a potential biomarker for HCC ( 71 ).…”
Section: Post-translational Modifications (Ptms) Of Hccmentioning
confidence: 99%